Regulation of Bacteriophage P22 DNA synthesis and repressor levels in P22cly infections. - Tokuno, S I (1977)
A rifampin-resistant mutant of Salmonella typhimurium carries an altered RNA polymerase. Wild-type (c+) phage P22 displays clear plaques and a reduced lysogenization frequency on this mutant host. The cly mutants of P22 were isolated on the basis of their ability to lysogenize such mutant hosts. Two classes of regulatory events, both of which are dependent on P22 gene c1 activity, are necessary for the establishment of lysogeny in P22. The positive events culminate in repressor synthesis; the negative events cause a retardation in phage DNA synthesis. Neither the positive nor the negative events are observed in P22c+ infections of the mutant host. Both effects are found in P22cly infections of the mutant host. Observable results of both the negative and the positive events are exaggerated in P22cly infections of wild-type hosts as compared to P22c+ infections. The cly mutation apparently increases the positive and negative regulatory events so that they are detectable in the mutant host and exaggerated in wild-type hosts. Possible mechanisms that result in the high frequency of lysogenization that characterizes the cly mutation and the nature of the cly mutation are discussed.